Non-steroidal anti-inflammatory drugs are not associated with increased risk of Clostridioides difficile infection: A propensity-score-matched case-control study. (December 2021) - Ressler, Adam M.; Patel, Alieysa; Rao, Krishna
Abstract: Prior research identified an increased risk for Clostridioides difficile infection (CDI) following exposure to certain non-steroidal anti-inflammatory drugs (NSAIDs). We conducted a retrospective case-control study to evaluate the risk for CDI associated with NSAID use. NSAID use was not associated with an increased risk of CDI. Highlights: Retrospective case control study of NSAIDs and risk for Clostridioides difficile Propensity score matching used to account for treatment assignment bias Included assessment of over the counter NSAID medication use with text based query No association was found between NSAIDs and Clostridioides difficile infection Multiple sensitivity and secondary analyses support the primary conclusion